Development of starch-gelatin complex microspheres as sustained release delivery system - B N Vedha Hari; T Praneetha; T Prathyusha; K Mounika; D Ramya Devi (Wolters Kluwer Medknow Publications, 2012)
The starch was isolated from jackfruit seeds and evaluated for its preformulation properties, like tapped density, bulk density, and particle size. The fourier transform infrared (FTIR) analysis was done and compared with that of the commercially available starch which confirmed the properties. Using the various concentrations of jackfruit seed starch, the microspheres were prepared, combining with gelatin by ionotropic gelation technique. The developed microspheres were subjected to analysis of particle size, drug content, entrapment efficiency, and percentage yield. The spectral analysis confirmed the presence of drug and absence of interactions. Scanning electron microscope image showed that the particles were in spherical shape with a rough surface. The in vitro drug release in water for 12 hours proved to be in the range of 89 to 100%. The various kinetic models were applied using release data to confirm the mechanism of drug. It was concluded that the jackfruit starch-gelatin microspheres gave satisfactory results and met pharmacopieal limits.